An Integrative Approach to Teaching Students to Understand Fine Art Samples - Abatov Jalgasbay Orinbaevich (Zien Journals, 2023)
The article reflects on how to explain examples of fine art to students, teach them to understand any work of art. Since each phenomenon is associated with time, samples of fine art also represent a certain period, historical or social event, in this sense, when understanding historical paintings, miniatures, unique canvases, it is also necessary to know the history with which a particular work of art is associated, or the historical range as a whole.. The article analyzes the problem of the application of integrative approaches to the understanding of samples of fine art.
Keywords: Fine art; literature; history; integration